2007
DOI: 10.1289/ehp.9887
|View full text |Cite
|
Sign up to set email alerts
|

Positive Associations of Serum Concentration of Polychlorinated Biphenyls or Organochlorine Pesticides with Self-Reported Arthritis, Especially Rheumatoid Type, in Women

Abstract: BackgroundPersistent organic pollutants (POPs) can influence the immune system, possibly increasing the risk of rheumatoid arthritis (RA). In addition, as metabolic change due to obesity has been proposed as one mechanism of osteoarthritis (OA), POPs stored in adipose tissue may be also associated with OA.ObjectiveOur goal in this study was to examine associations of background exposure to POPs with arthritis among the general population.DesignWe investigated cross-sectional associations of serum POPs concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 36 publications
1
56
0
Order By: Relevance
“…Joint conditions have been associated with contextual factors including pollutants, mechanical factors affecting the hands (e.g., occupational load), poverty and low education [44][45][46]. Lee and colleagues further note that obesity can contribute to joint problems [46], suggesting that factors driving differences in obesity levels might also be responsible for higher frequency of joint disease. We tested this link and found that BMI is significantly associated with joint disease in our sample (analyses available upon request).…”
Section: Discussionmentioning
confidence: 99%
“…Joint conditions have been associated with contextual factors including pollutants, mechanical factors affecting the hands (e.g., occupational load), poverty and low education [44][45][46]. Lee and colleagues further note that obesity can contribute to joint problems [46], suggesting that factors driving differences in obesity levels might also be responsible for higher frequency of joint disease. We tested this link and found that BMI is significantly associated with joint disease in our sample (analyses available upon request).…”
Section: Discussionmentioning
confidence: 99%
“…A weak association has also been reported for organochlorine pesticides exposure and rheumatoid arthritis (RA, Relative Risk 2) [63,64]. In the Women's Health Initiative Observational Study (76.861 postmenopausal women enrolled, aged 50-79 years), personal use of insecticides was associated with an increased risk of RA and SLE.…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 99%
“…Exposure to PCBs has been linked to RA: in a 2007 cross-sectional study, serum concentration of PCBs was positively associated with a self-reported diagnosis of RA (OR 2.2) [63]. Concerns of immune alterations in PCB-exposed humans have also been raised: in a study in Dutch children, PCB levels were tied to an increased prevalence of ear infections and chickenpox with lowered immune system function [66].…”
Section: Effects Of Environmental Estrogens On the Immune Systemmentioning
confidence: 99%
“…However, shared mechanisms may provide links to RA; for example, endocrine disruption, inflammation, and stress response (40)(41)(42). In a US population sample (1999)(2000)(2001), organochlorine levels were elevated in women with self-reported RA (43). Early research in the Agricultural Health Study cohort showed no association of RA in women reporting use of DDT, but the study included only 135 cases (mostly prevalent) (44).…”
Section: Discussionmentioning
confidence: 98%